Quantitative Elasticity Mapping of Submicron Silica Hollow Particles by PeakForce QNM AFM Mode - Dmitry R. Streltsov; Kirill M. Borisov; Aleksandra A. Kalinina; Aziz M. Muzafarov (Nanomaterials, 2023)
Silica hollow spheres with a diameter of 100–300 nm and a shell thickness of <semantics>8±2</semantics> nm were synthesized using a self-templating amphiphilic polymeric precursor, i.e., poly(ethylene glycol)-substituted hyperbranched polyethoxysiloxane. Their elastic properties were addressed with a high-frequency AFM indentation method based on the PeakForce QNM (quantitative nanomechanical mapping) mode enabling simultaneous visualization of the surface morphology and high-resolution mapping of the mechanical properties. The factors affecting the accuracy of the mechanical measurements such as a local slope of the particle surface, deformation of the silica hollow particles by a solid substrate, shell thickness variation, and applied force range were analysed. The Young’s modulus of the shell material was evaluated as <semantics>E=26±7</semantics> GPa independent of the applied force in the elastic regime of deformations. Beyond the elastic regime, the buckling instability was observed revealing a non-linear force–deformation response with a hysteresis between the loading and unloading force–distance curves and irreversible deformation of the shell at high applied forces. Thus, it was demonstrated that PeakForce QNM mode can be used for quantitative measurements of the elastic properties of submicon-sized silica hollow particles with nano-size shell thickness, as well as for estimation of the buckling behaviour beyond the elastic regime of shell deformations.